Дослідження пізньопалеолітичної стоянки біля с. Кам’янка у 2010–2012 роках - Сніжко, І. А. (Давнина. Харківський історико-археологічний щорічник, 1970)
РезюмеСнежко И. А. Исследования позднепалеолитической стоянки у с. Каменка в 2010–2012 годахСтоянка расположена на мысу при впадении в р. Северский Донец правого притока р. Сухая Каменка в 1,5 км на юго-восток от с. Каменка Харьковской области. Открыта в 2004 г., в 2005–2009 гг. сплошной площадью исследовано 78 кв. м, коллекция насчитывает свыше 4,5 тыс. предметов. Настоящая публикация посвящена результатам работ 2010–2012 гг. — исследованная площадь увеличилась на 43 кв. м, коллекция пополнилась более 2 тыс. артефактов. Культурный слой залегает на стыке древнеголоценовой почвы и причерноморского лёсса, содержит кремневые артефакты, кусочки охры и мелкие фрагменты костей. Кремневые изделия представляют полный цикл расщепления, характерный для стоянок, расположенных недалеко от источников сырья. Время существования памятника находится в пределах перехода от раннепричерноморского стадиала к концу позднеледниковья.Ключевые слова: поздний палеолит, стоянка у с. Каменка, культурный слой. SummaryI. Snizhko. The Late Paleolithic site Research Near the Kamyanka Village in 2010–2012The site is situated on a cape at the place where the Sykhaya Kamyanka right tributary flows into the Seversky Donets river. It is 1.5 km to south-east from the Kamyanka village of the Kharkiv region. The site was discovered in 2004; the solid territory of 78 sq. m was researched in 2005–2009. The collection consists of more than 4.5 items. The present publication covers the research results of 2010–2012. The investigation territory grew to 43 sq. m, the collection enriched with 2000 artifacts. The cultural layer lies in the ancient Holocene soil and the Black sea maritime aeolian soil, junction, it contains flint artifacts, pieces of ochre and small bone fragments. The flint artifacts represent the full splitting cycle which is typical for the sites that are situated near the source of the raw material. The site time frames are in the period of conversion from the Black sea maritime to the end of the late glacial.Key words: late Paleolithic, site, the Kamyanka village near the Kharkiv region, cultural layer, planigraphy.